Role of BRCA1 in Diagnosis of Triple Negative Breast Cancer - Husni Aref, Nuran (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Triple-negative (TN) tumors are considered to be the most common subtype breast cancer in individual who carry BRCA1 mutation. in the recent years BRCA1 testing was advised to be offered to all individuals who are below 50 years and whom carry Triple negative breast cancer. Furthermore BRCA1 mutation frequency and the amplification for clinical practice of undertaking genetic testing in women with TN breast cancer have been evaluated.
Breast cancer is a type of cancer that starts in the breast, when cells begin to grow out of control, and Breast cancer cells usually form a tumor that can often be seen on an x-ray or felt as a lump. Breast cancer occurs almost entirely in women, but men can get breast cancer, too. TNBC (Triple Negative Breast Cancer) is cancer that tests negative for three hormones receptors, estrogen receptors, progesterone receptors, and have little or no HER2 protein expression. (5,6) The lacking of expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor (HER2) describe the TNBC ( Triple Negative Breast Cancer ) which is a subgroup of tumors(1) , However, TNBC ( Triple Negative Breast Cancer ) are a collection of different breast cancers that are still poorly characterized at the molecular level, and lack definitive prognostic markers and selective targets of therapy(2) . Although its incidence is still high, the overall mortality due to breast cancer has decreased, in addition, it accounts for about 15% of all breast cancers, and it occurs more in younger women than the older ones and it occurs more frequently in individuals with a germline BRCA1 mutation.(3)